A novel CRISPR-based malaria diagnostic capable of Plasmodium detection, species differentiation, and drug-resistance genotyping - Cunningham, Clark H.; Hennelly, Christopher M.; Lin, Jessica T.; Ubalee, Ratawan; Boyc, Ross M.; Mulogo, Edgar Mugema; Hathaway, Nicholas; Thwai, Kyaw L.; Phanzu, Fernandine; Kalonji, Albert; Mwandagalirwa, Kashamuka; Tshefu, Antoinette; et al. (BioMedicine, 2021)
Background: CRISPR-based diagnostics are a new class of highly sensitive and specific assays with multiple applications in infectious disease diagnosis. SHERLOCK, or Specific High-Sensitivity Enzymatic Reporter UnLOCKing, is one such CRISPR-based diagnostic that combines recombinase polymerase pre-amplification, CRISPR-RNA base-pairing, and LwCas13a activity for nucleic acid detection. Methods: We developed SHERLOCK assays capable of detecting all Plasmodium species known to cause human malaria and species-specific detection of P. vivax and P. falciparum, the species responsible for the majority of malaria cases worldwide. We further tested these assays using a diverse panel of clinical samples from the Democratic Republic of the Congo, Uganda, and Thailand and pools of Anopheles mosquitoes from Thailand. In addition, we developed a prototype SHERLOCK assay capable of detecting the dihydropteroate synthetase (dhps) single nucleotide variant A581G associated with P. falciparum sulfadoxine resistance. Findings: The suite of Plasmodium assays achieved analytical sensitivities ranging from 25-188 parasites per reaction when tested against laboratory strain genomic DNA. When compared to real-time PCR, the P. falciparum assay achieved 94% sensitivity and 94% specificity during testing of 123 clinical samples. Compared to amplicon-based deep sequencing, the dhps SHERLOCK assay achieved 73% sensitivity and 100% specificity when applied to a panel of 43 clinical samples, with false-negative calls only at lower parasite densities. Interpretation: These novel SHERLOCK assays demonstrate the versatility of CRISPR-based diagnostics and their potential as a new generation of molecular tools for malaria diagnosis and surveillance
Keywords: SHERLOCK; Malaria; CRISPR; Cas13a; Diagnostic